PREFERENSI KONSUMEN TERHADAP BUAH-BUAHAN LOKAL DAN ORGANIK SERTA IMPLIKASINYA TERHADAP PENDIDIKAN KONSUMEN CINTA PRODUK NASIONAL - Sumarwan, Ujang; Palupi, Eny (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2017)
The objectives of the study were to analyze factors influencing preferences towards fruits and to measure consumer preference on the three attributes of fruits which is a type of fruit, fruit origin (local and imported), as well as the way of cultivation (organic and non-organic) fruits and determine what attributes are more preferred by consumers. The study involved 391 respondents students of the Bogor Agricultural Institute who were selected by convenience sampling technique. The survey was conducted by direct interview using a questionnaire with structured questions and choices. Data were analyzed using multiple regression and conjoint analyses. The results showed that the respondents have the highest preference to attribute cultivation of organic fruits, followed by aspects of the locality and the type of fruit. Respondents preferred organic fruit as compared to non-organic fruit, local fruit is more desirable than the imported fruit. The results of this study provide important implications for consumer education to love national fruit products. Consumer preferences towards local and organic fruits need to be maintained and enhanced through consumer education. Consumer education is necessary to build a spirit of love national fruit products and to increase consumer knowledge about the benefits of organic fruits.